Efektivitas Metode Bruner dalam Meningkatkan Kemampuan Mengenal Lambang Bilangan pada Anak Down Syndrom - Rahmi, Welia Yerida; Mahdi, Arisul; Iswari, Mega; Kusumastuti, Grahita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article discusses the effectiveness of the Bruner method in improving the ability to recognize number symbols in children with Down syndrome. The subject of this study was a child with Down syndrome who experienced difficulties in recognizing number symbols. This study used a quantitative approach with an experimental research method in the form of single subject research (SSR) with an A-B research design. The data collection technique in this study was a test. The data analysis technique used visual graphic analysis. This study was conducted in 19 meetings. The data obtained in each condition, namely the baseline phase, was carried out in 4 meetings with a percentage of 40%, 40%, 40%, 40%. In the intervention condition as many as 15 meeting with the percentage of each meeting obtained is 45%, 45%, 55%, 55%, 65%, 65%, 75%, 75%, 75%, 80%, 85%, 90%, 90%, 90%, 90%based on the results of the research that has been done proves that the Bruner method is effective in improving the ability to recognize number symbols in children with Down syndrome at SLB Autisma YPPA Solok.